Synthesis and Electrochemical Improvement of Nanocrystalline LiMn2-XMgXO4 Powder Using Sol-Gel Method - K.Suryakala, G.Paruthimal Kalaignan and T.Vasudevan (International Journal of Electrochemical Science, 2006)
With the advancement of nanotechnology, there is an interest in the replacement of conventional materials by nanomaterials. There is a reasonable chance that as the active mass of electrode for lithium batteries is comprised of smaller particles, they will perform better in terms of capacity, power, rate capability and stability. The “bottom–up” approach of LiMn2-XMgXO4 (X=0.5) Nano material was synthesized and characterized by electrochemical techniques. LiMn2O4 is inexpensive material but it shows rather poor cyclic performance. The electrochemical performance of spinel type LiMn2O4 has been effectively improved with doping of Mg by Sol-Gel method. Their structural and textural properties of LiMn2-XMgXO4 (X=0.5) was determined by using X-ray diffraction (XRD), Transmission electron microscopy (TEM), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA), Cyclic Voltammetry technique was used to characterize the reversibility of the cathode material. Cells made from the spinels have exhibited good rate of performance at C/10 rate charge – discharge studies.